Petrology, Mineralogy and Diagenesis of the Rus and Jil Formations (l- Eocene) in Najif and Samawa areas, Southern Iraq - Tamar-Agha , Mazin Y.; Saleh , Safaa Adeeb (Iraqi Journal of Science, 2022)
This research deals with study of the Petrology and mineralogy of the Rus and Jil Formations at Najif and Al-Muthanna Governorates, Southern Iraq. The Rus Formation consists mainly of evaporites and subordinate carbonates. The evaporites are characterized by nodular structure (compound wispy, wispy, structureless and mosaic structures) with some laminated structure at the studied sections. Compound wispy to wispy structure are the dominant structures. The Jil Formation consists almost entirely of carbonate. The carbonate rocks are dolomitic limestone and dolomite beds, massive, fossiliferous, cavernous sometime friable and bioturbated in its lower part. The Jil Formation contains evaporites as thin beds, sometimes nodular and contains selenite gypsum and very thin veins of satin-spar.X-ray diffractometry reveals that the non-clay minerals are dominantly dolomite, gypsum and calcite. The clay minerals present in the Rus Formation are: illite, smectite, chlorite and kaolinite. In the Jil Formation the main clay minerals are illite and smectite. The clay minerals are referring to climate arid to semi arid.